Bacterial and fungal characterization of pancreatic adenocarcinoma from Endoscopic Ultrasound-guided biopsies - Wright, Robin D.; Bartelli, Thais F.; Baydogan, Seyda; White, James Robert; Kim, Michael P.; Bhutani, Manoop S.; McAllister, Florencia (Frontiers in Immunology, 2023)
The tumor microbiome (TM) has been linked to pancreatic cancer prognosis. Specific microbes can confer tumor resistance to therapies. Early knowledge of the TM at time of diagnosis would be clinically relevant for precision therapy based on microbial composition. However, it is difficult to define the TM prior to surgical resection. In this pilot feasibility study, patients underwent Endoscopic Ultrasound-Fine Needle Aspiration (EUS-FNA) biopsy of pancreatic adenocarcinoma. These samples were analyzed using 16S rRNA and internal transcribed spacer (ITS) sequencing for characterization of the tumor bacteria and fungi. After in silico decontamination and comparison to non-matched tumor, we were able to characterize the TM in biopsies, which was comparable to TM from surgical specimens. EUS-FNA biopsy may represent a feasible modality to characterize the pancreatic TM.